2021
DOI: 10.1186/s12906-021-03215-3
|View full text |Cite
|
Sign up to set email alerts
|

A network pharmacology perspective for deciphering potential mechanisms of action of Solanum nigrum L. in bladder cancer

Abstract: Background Solanum nigrum L. decoction has been used as a folklore medicine in China to prevent the postoperative recurrence of bladder cancer (BC). However, there are no previous pharmacological studies on the protective mechanisms of this activity of the plant. Thus, this study aimed to perform a systematic analysis and to predict the potential action mechanisms underlying S. nigrum activity in BC based on network pharmacology. Methods Based on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 78 publications
(110 reference statements)
0
17
0
2
Order By: Relevance
“…in the Solanaceae . Modern studies have found that nightshade produces an anti-tumor effect and it has been extensively employed in treating multiple tumors [ 4 ]. Existing research results have shown that the anti-tumor mechanisms of nightshade mainly include blockage of the cell cycle, inhibition of cell proliferation and tumor growth, induction of cell apoptosis, and inhibition of epithelial-mesenchymal transformation and tumor metastasis [ 5 ], thereby enhancing the efficacy of radiotherapy, chemotherapy, targeted therapy, and reversal of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…in the Solanaceae . Modern studies have found that nightshade produces an anti-tumor effect and it has been extensively employed in treating multiple tumors [ 4 ]. Existing research results have shown that the anti-tumor mechanisms of nightshade mainly include blockage of the cell cycle, inhibition of cell proliferation and tumor growth, induction of cell apoptosis, and inhibition of epithelial-mesenchymal transformation and tumor metastasis [ 5 ], thereby enhancing the efficacy of radiotherapy, chemotherapy, targeted therapy, and reversal of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is evolving as a frontier in drug discovery and development as it integrates systematic medicine with information science [ 14 ]. In the beginning, network pharmacology had a vague conception about drug discovery, and perhaps some overhyping of its promises, as found in the early stages of almost all new technologies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are more than 20 species forming the Solanum nigrum L. complex species system, of which four species are mainly distributed in China, namely; Lobelia, Lobelia olivacea, Lobelia yellow-fruited and Lobelia red-fruited ( 22 ). Solanum nigrum L. exhibits anti-tumor activities, particularly against breast and bladder cancers ( 23 , 24 ). It has also been shown to be effective in the treatment of colitis ( 25 ), inhibition of liver fibrosis, and exhibits anti-hepatitis virus ( 26 ), hepatoprotective ( 27 ), antipyretic and analgesic ( 28 ), as well as antihypertensive effects.…”
Section: Introductionmentioning
confidence: 99%